Gender variability issues of modern women`s sports - Sobolev, D. V.; Sysoyev, A. V.; Soboleva, T. S. (Theory and Practice of Physical Culture, 2019)
Historically the women`s sports have largely been viewed as derivatives of the men`s ones. Individual sport predispositions are commonly considered driven by the gender-unspecific physical activities (hyperkinesia) largely formed in the prenatal development period. Objective of the study was to analyze the inborn predispositions to a high physical activity (hyperkinesia) in women on the following assumptions. On the one hand, the individual predisposition to sports depends on the testosterone-driven gender-unspecific physical activities (hyperkinesia) formed in the prenatal development period. Some females are diagnosed with hyperandrogenism, which is the increased synthesis of testosterone (androgen) by adrenal associated with the male-type cerebral differentiation process and male developmental programs taking the lead in every bodily system. On the other hand, the modern women`s sports face multiple challenges due to the transgender human resource inflow promoted and supported by some vested interests.